Development of a Methylene Blue Carrier System in Gellan Gum for Application in Antimicrobial Photodynamic Therapy against Candida albicans - Mendes, Gabriela Vieira [UNESP]; Godoi, Lívia Mara Alves Figueiredo [UNESP]; Morissugui, Éric Yukio [UNESP]; de Souza Santos, Evelyn Luzia [UNESP]; Fraga, Amanda Siqueira [UNESP]; Tada, Dayane Batista; Garcez, Aguinaldo S.; Garcia, Maíra Terra [UNESP]; Arumugam, Ganeshkumar [UNESP]; Junqueira, Juliana Campos [UNESP] (American Chemical Society (ACS), 2025)
Candidiasis is a common infection primarily caused by the opportunistic fungus Candida albicans . Conventional antifungals have been associated with several limitations, and today, antimicrobial photodynamic therapy (aPDT) is raised as an adjuvant treatment. This study aimed to develop a carrier system for the photosensitizer methylene blue (MB) based on a gellan gum (GG) hydrogel, a nontoxic exopolysaccharide. Two formulations consisting of 0.6% and 1.0% (w/v) GG containing MB were prepared and characterized in relation to release kinetics, absorption spectroscopy, and optical shield formation. Then, the effects of MB GG formulations in aPDT using LED irradiation were evaluated against C. albicans. For this, aPDT was applied toC. albicans in planktonic and biofilm stages and also tested in a Galleria mellonella burn infection model. The successful incorporation of MB into the GG hydrogel was confirmed by absorption spectroscopy, with a characteristic peak at 660 nm for intact MB and both GG formulations. The GG0.6% hydrogel released 100% of MB in 12 min, whereas the GG1.0% hydrogel released only 75% of MB after 25 min. Furthermore, no optical shield formation was noticed with the MB gellan formulations in comparison to the aqueous form. In relation to antifungal activity on C. albicans, aPDT with GG0.6% and GG1.0% containing MB led to an eradication of planktonic cells and a partial reduction of biofilms, as observed in aPDT with MB aqueous. When aPDT was applied in G. mellonella larvae, an increase of 50% and 30% in survival rate was found, respectively, for the groups treated with MB gellan formulation and MB aqueous. In conclusion, the gellan gum formulations designed here were able to release MB and maintain its optical and photodynamic properties against C. albicans. In addition, aPDT with MB gellan formulations had higher in vivo efficacy than MB aqueous.